Microstructural map of a thin-section scale fold pair; implications for folding mechanism in a fine-grained garnet - Aerden, D.; Aldaher, S.; Bouybaouene, M.; Sayab, M. (TRABAJOS DE GEOLOGÍA, 2009)
Detailed microstructural mapping of thin section-scale folds in a garnet bearing micaschist sample from the RIF Mountains (Morocco), including analysis of inclusion trails in 62 small garnets, reveals interesting details about the folding mechanism. A number of classic fold mechanisms capable of producing axial-plane cleavage are reviewed and shown to insufficiently explain the mapped microstructural patterns including cleavage fanning, wedge-shaped microlithons, and detailed crenulation geometries associated with different stages of compositional differentiation (S2). A new model is proposed in which crenulation cleavage evolves from initial conjugate kink bands to sets of closely spaced micro-shear zones with major shortening components.